Fasād fī al-Arḍ and Illegal Gold Mining in Jambur Tarutung: An Ecological Reading of Tafsir al-Munir - Reski Gosali; Achyar Zein (Sinthop: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2026)
Illegal gold mining, known in Indonesia as Pertambangan Emas Tanpa Izin (PETI), has generated serious ecological and social consequences in rural communities. Although Islamic environmental ethics and ecological tafsir have received growing scholarly attention, many studies remain normative and have not sufficiently connected Qur’anic exegesis with empirical ecological realities. This article examines ecological degradation caused by PETI in Lingkungan III Jambur Tarutung, Pasar Kotanopan Village, Mandailing Natal Regency, North Sumatra, through the concept of fasād fī al-arḍ in Tafsir al-Munir by Wahbah az-Zuhaili. The study employed a qualitative case study design combined with thematic Qur’anic interpretation (tafsīr maudhu‘i). Primary data were collected through field observations and semi-structured interviews with six purposively selected informants, consisting of community leaders, religious leaders, and community members connected to mining-related activities. Secondary data were obtained from Tafsir al-Munir, ecological tafsir literature, maqāṣid al-sharī‘ah studies, and previous research on illegal mining and environmental degradation. The findings show that PETI has altered river conditions, increased sedimentation, degraded agricultural land, resulted in unreclaimed mining pits, intensified livelihood vulnerability, and affected patterns of religious and community participation. From the perspective of Tafsir al-Munir, these impacts represent fasād fī al-arḍ because they disrupt ecological balance, weaken public welfare, and reflect the failure to uphold human responsibility as khalīfah. This article argues that Tafsir al-Munir provides a contextual ethical framework for interpreting local ecological degradation and linking environmental responsibility with social welfare, moral accountability, and ecological restoration.